2021
DOI: 10.3389/fmicb.2021.736066
|View full text |Cite
|
Sign up to set email alerts
|

The SNARE Protein CfVam7 Is Required for Growth, Endoplasmic Reticulum Stress Response, and Pathogenicity of Colletotrichum fructicola

Abstract: The tea-oil tree Camellia oleifera is native to China and is cultivated in many parts of southern China. This plant has been grown for over 2,000 years, mainly for its high-quality cooking oil. Anthracnose is the main disease of tea-oil tree and results in a huge loss annually. Colletotrichum fructicola is a major pathogen causing anthracnose on tea-oil tree. In a previous study, we characterized that the bZIP transcription factor CfHac1 controlled the development and pathogenicity of C. fructicola. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, the ∆ Clpls1 mutants of C. lindemuthianum do not have defects in formation and maturation of the appressorium but may be deficient in the formation and/or positioning of the penetrating pore and therefore also lose pathogenicity [ 29 ]. In previous studies on C. fructicola we found that the CfGCN5 , CfVPS39 , and CfVAM7 genes were involved in the regulation of appressorium development and the mutants completely lost their pathogenicity [ 1 , 30 , 31 ]. In this study, the appressorium formation rate of the ∆ Cfvps35 mutant was significantly reduced and its collapse rate was higher than that of the WT and complemented strain.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ∆ Clpls1 mutants of C. lindemuthianum do not have defects in formation and maturation of the appressorium but may be deficient in the formation and/or positioning of the penetrating pore and therefore also lose pathogenicity [ 29 ]. In previous studies on C. fructicola we found that the CfGCN5 , CfVPS39 , and CfVAM7 genes were involved in the regulation of appressorium development and the mutants completely lost their pathogenicity [ 1 , 30 , 31 ]. In this study, the appressorium formation rate of the ∆ Cfvps35 mutant was significantly reduced and its collapse rate was higher than that of the WT and complemented strain.…”
Section: Discussionmentioning
confidence: 99%
“…The gene was downregulated in YSB and MM in 3D1 compared to 3D7, demonstrating that transcription of this gene varies between the parents. Vacuoles play important roles in both osmotic stress responses (Richards et al, 2010) and virulence (Li et al, 2021). Under salt stress the vacuoles can undergo fusion and fission – changing in size and number (Richards et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the appressorium formation rate of the Δ Cfvps29 mutant was significantly reduced. In previous studies on C. fructicola , we found that the CfSNF1 , CfGCN5 , CfVPS39 , and CfVAM7 genes were involved in the regulation of appressorium development, and the mutants completely lost their pathogenicity [ 6 , 8 , 9 , 10 ]. CfVps29 may therefore be important for pathogenicity through its regulatory role in appressorium formation.…”
Section: Discussionmentioning
confidence: 99%
“…Chitin and glucan are two major components of the fungal cell wall. In plant pathogenic fungi, the development of the invasion structure, the growth, and morphology of mycelia depend on the regular synthesis and distribution of chitin in the cell wall [ 10 , 11 , 12 ]. In the rice blast fungus M .…”
Section: Discussionmentioning
confidence: 99%